PENGATURAN UU BAGI PEDAGANG KAKI LIMA UNTUK MENGENDALIKAN PENJUALAN SEMBARANGAN (STUDI KASUS: PEDAGANG KAKI LIMA GERBANG 4 UNIMED) - Adelina Martha Aritonang; Eka Putriani Sihombing, Ertika Susanti Pasaribu, Herlide Purba, Iwain Oktaviona Nababan, Pebryna Rio (CV. Adiba Aisha Amira, 2024)
Street vendors are an important part of the urban economy in many countries. However, indiscriminate sales by street vendors can cause problems related to cleanliness, health and spatial planning. Therefore, legal regulations (UU) are needed to control indiscriminate sales. This research aims to analyze the impact of legal regulations on street vendors and the surrounding environment. Literature studies show that several countries have succeeded in implementing effective regulations to control indiscriminate sales by street vendors. For example, in Singapore, street vendors must adhere to strict regulations regarding cleanliness and layout. In Indonesia, several cities have implemented regulations regarding distance between traders and restrictions on the types of goods sold. The results of this research can provide guidance for the government in designing effective regulations to control indiscriminate sales by street vendors, so as to improve cleanliness, health and urban spatial planning. Thus, proper regulation of the law can provide benefits for street vendors and society as a whole, by ensuring the sustainability of street vendors' businesses while still paying attention to the public interest.